A Market Separation Theory of Rent Differentials in Metropolitan Areas - Haugen, Robert A.; Heins, A. James (Quarterly Journal of Economics, 1969)
The general model, 660. — The regression model, 663. — Correlation and regression results, 666. — Evaluation, 667. — Some conclusions, 670. — Appendix, 671.